2013
DOI: 10.1111/iej.12202
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm removal by 6% sodium hypochlorite activated by different irrigation techniques

Abstract: Laser activation of 6% sodium hypochlorite significantly improved the cleaning of biofilm-infected dentine followed by passive ultrasonic irrigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 34 publications
8
86
0
7
Order By: Relevance
“…Techniques which are commonly used, such as paper point sampling followed by CFU counting can determine general bacterial counting from the coronal third which can exclude information from the apical third, where disinfection is more indicative of irrigation efficiency and more difficult to access. Measurement of the apical third cleanliness has been attempted by direct-access methods, as well as split-model methods, both requiring structural modification of the dentin and apical complexities [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. While the method used in this experiment contains similar shortcomings to the paper point/CFU method with regards to sampling location, it provides expeditious sample collection, reuse of samples in order for the same sample to serve as a control, and a well-known, reliable methodology for bacterial quantification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Techniques which are commonly used, such as paper point sampling followed by CFU counting can determine general bacterial counting from the coronal third which can exclude information from the apical third, where disinfection is more indicative of irrigation efficiency and more difficult to access. Measurement of the apical third cleanliness has been attempted by direct-access methods, as well as split-model methods, both requiring structural modification of the dentin and apical complexities [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. While the method used in this experiment contains similar shortcomings to the paper point/CFU method with regards to sampling location, it provides expeditious sample collection, reuse of samples in order for the same sample to serve as a control, and a well-known, reliable methodology for bacterial quantification.…”
Section: Discussionmentioning
confidence: 99%
“…Laser activation of intracanal irrigant creates large elliptical vapor bubbles that expand and subsequently implode, causing a cavitation and shock wave effect that promotes debridement and smear layer removal and the release of energy further down the canal [16]. Previous studies have shown PIPS to be effective in biofilm elimination [17], smear layer removal [16], and debris removal from complex nonseparated systems [18]. Apical size and taper size have been studied in the past by multiple studies, with varying conclusions reflecting the needs of obturation and irrigation techniques [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Tijekom pasivnoga ultrazvučnog ispiranja (PUI) energija se prenosi s oscilirajućeg nastavka na sredstvo za ispiranje, uzrokujući stvaranje ultrazvučnih valova u tekućini (10). Pasivno ultrazvučno ispiranje pokazalo se učinkovitim u uklanjanju zaostatnog sloja i debrisa (11) te intrakanalnog biofilma (12). Sistem RinsEndo ® (Dürr Dental GmbH & Co., Bietigheim-Bissingen, Njemač-ka) automatski je sustav čije se djelovanje temelji na tehnologiji pritiska i povlačenja te na aktivaciji sredstva za ispiranje u korijenskom kanalu (1,5 Hz).…”
Section: Uvodunclassified
“…The PUI has been reported to be efficient in the removal of intracanal smear layer and debris (11), and to facilitate the disruption of endodontic biofilms (12). The RinsEndo ® (Dürr Dental GmbH & Co., Bietigheim-Bissingen, Germany) is an automated system which uses pressure-suction technology to deliver the irrigant solution in the root canal and activates it automatically (1.5 Hz).…”
Section: Izbor I Priprema Uzorakamentioning
confidence: 99%
“…Studies have shown that PUI with NaOCl could not only effectively remove the smear layer inside infected root canals but also significantly improve the cleaning of biofilm-infected dentine (George et al, 2008;De Moor et al, 2010;Ordinola-Zapata et al, 2014). For PUI, however, the apical third of a root canal should be enlarged to at least an International Organization for Standardization (ISO) size of 35-40 to allow needle placement to within 1-2 mm of the apical seat (Huang et al, 2008;Peeters & Gutknecht, 2014), which might limit its application.…”
Section: Introductionmentioning
confidence: 99%